Early dual antiplatelet therapy (DAPT) administration within 6 h post-coronary artery bypass grafting (CABG): an audit, pilot study, and follow-up analysis - Yen Chuan Chen; Khairul Anuar Abdul Aziz; Mohamed Ezani Md Taib; Alwi Mohamed Yunus; Intan Fariza Gaaffar (The Cardiothoracic Surgeon)
Abstract Background The optimal timing for administering dual antiplatelet therapy (DAPT) post-coronary artery bypass grafting (CABG) remains a subject of debate. This study aimed to evaluate the safety and efficacy of early DAPT administration within 6 h post-CABG, following the implementation of a new standard operating procedure (SOP). This study was conducted in three phases at the National Heart Institute of Malaysia. Phase 1 involved a clinical audit of 80 isolated CABG patients to evaluate current DAPT practices. Phase 2 was a pilot study involving 320 patients to establish criteria for early DAPT initiation. Phase 3 comprised a prospective cohort analysis comparing outcomes between 939 propensity-matched pairs receiving early/new SOP (< 6 h) and late/old SOP (> 6 h) DAPT. Results The clinical audit revealed a mean DAPT administration time of 18.3 h post-CABG, highlighting variability in practice. The pilot study demonstrated that early DAPT was associated with a significantly lower chest reopening rate (0.8% vs. 21.6%) under stringent selection criteria. In the follow-up study, early DAPT was linked to reduced rates of postoperative stroke (1.0% vs. 2.5%, p = 0.013), dialysis (5.5% vs. 7.0%, p < 0.001), and chest reoperation (6.5% vs. 9.0%, p = 0.045). Despite a higher transfusion rate in the early DAPT group (76.0% vs. 43.6%, p < 0.001), ICU stays and hospitalization durations were not prolonged. Mortality rates were lower in the early DAPT group (3.2% vs. 4.6%), although the difference was not statistically significant (p = 0.123). Conclusions Guided by stringent clinical criteria, early DAPT administration within 6 h post-CABG is a feasible and effective strategy for reducing adverse outcomes, such as stroke and dialysis requirements, while maintaining manageable bleeding risks. Future research should explore long-term graft patency, refine transfusion protocols, and assess the broader applicability of this approach.